2013
DOI: 10.1097/jsa.0b013e318272f530
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy Management of Knee Osteoarthritis in the Middle-aged Athlete

Abstract: Osteoarthritis (OA) is prevalent in today's population, including the athletic and recreationally active "middle-aged" population. OA is a degenerative condition of the articular/hyaline cartilage of synovial joints and commonly affects the knee joint. In general, athletic participation does not specifically influence a higher incidence of knee OA in this population; however, traumatic injury to the knee joint poses a definitive risk in developing early-onset OA. The purpose of this article is to review eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…41 Several studies have reported positive effects from LLLT including influences on fibroblast propagation, osteoblast production, and collagen synthesis as well as revascularization in wound healing. 10 In addition, it has a positive effect on modulation of inflammation 13,14,42 and stimulation of angiogenesis as well as in the reduction of fibrosis formation. 15 Improvements of physical joint function outcomes usually occur as a consequence of pain intensity reduction, as pain reduction is usually primarily responsible for improvements in muscle function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Several studies have reported positive effects from LLLT including influences on fibroblast propagation, osteoblast production, and collagen synthesis as well as revascularization in wound healing. 10 In addition, it has a positive effect on modulation of inflammation 13,14,42 and stimulation of angiogenesis as well as in the reduction of fibrosis formation. 15 Improvements of physical joint function outcomes usually occur as a consequence of pain intensity reduction, as pain reduction is usually primarily responsible for improvements in muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…LLLT is considered a safe and applicable modality for patients with knee OA. 12,17,18 Its usage is supported either in middle-aged subjects 10 or for particular older subjects 12,23 where the usage of drugs is more restricted. Effects of LLLT on knee OA has been studied, but the results are still in conflict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knee osteoarthritis symptoms include joint pain, inflammation, and swelling [2]. Joint discomfort can impede the ability of the older adults to engage in daily and functional activities [1].…”
Section: Introductionmentioning
confidence: 99%
“…Joint discomfort can impede the ability of the older adults to engage in daily and functional activities [1]. Conservative treatments for knee osteoarthritis often involve physical therapy, weight control, and therapeutic exercise [2]. Therapeutic exercise, a widely accepted treatment approach, increases the muscle strength of the thighs, thereby enhancing joint stability and reducing cartilage loss in the knee [3].…”
Section: Introductionmentioning
confidence: 99%